(untitled) (Czech Journal of International Relations, 1992)
The author is writing about a statement that the world importance on the Middle East oil fields joint with economic and security factors to create a direct link between regional stability and international security. With the ending of the Cold War. The world needs a new conception for European security. The Kuwait crisis has confirmed the dominant role of the U.S. in the post-communist world and the military and political qualifications of its application, but only in the context of a more expensive international action. Therefore, a permanent control of regional conflicts demands at looking for new forms of control and regulation that would be valid the world over. The allied coalition against Iraq was purpose-made and could not become a base for a wider regional agreement. However, today’s Soviet-American regional cooperation is not very hopeful. It is necessary to look for a real complex peace solution from the beginning, even if the situation is relatively more stable.